2022
DOI: 10.1039/d2ra01900k
|View full text |Cite
|
Sign up to set email alerts
|

High-quality all-inorganic CsPbBr3 single crystals prepared by a facile one-step solution growth method

Abstract: High crystalline quality all-inorganic CsPbBr3 single crystals were obtained via a facile one-step solution growth method. The (002) X-ray rocking curve is as narrow as 0.043°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The all-inorganic perovskite CsPbBr 3 single crystals were prepared using a modified low-temperature one-step solution growth method according to a previous report (see Methods), where the CsPbBr 3 single crystals (Figure a inset) were obtained by heating the precursor solution in an oil bath at 140 °C (Figure S1, Supporting Information). It showed that the oil bath heating was critical for the improvement of crystalline quality and reduction of trap states ( n trap ∼ 5.1 × 10 9 cm –3 ) in the as-grown CsPbBr 3 single crystals Figure a depicts the typical X-ray diffraction (XRD) pattern of the as-grown CsPbBr 3 single crystal.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The all-inorganic perovskite CsPbBr 3 single crystals were prepared using a modified low-temperature one-step solution growth method according to a previous report (see Methods), where the CsPbBr 3 single crystals (Figure a inset) were obtained by heating the precursor solution in an oil bath at 140 °C (Figure S1, Supporting Information). It showed that the oil bath heating was critical for the improvement of crystalline quality and reduction of trap states ( n trap ∼ 5.1 × 10 9 cm –3 ) in the as-grown CsPbBr 3 single crystals Figure a depicts the typical X-ray diffraction (XRD) pattern of the as-grown CsPbBr 3 single crystal.…”
Section: Resultsmentioning
confidence: 99%
“…It showed that the oil bath heating was critical for the improvement of crystalline quality and reduction of trap states (n trap ∼ 5.1 × 10 9 cm −3 ) in the asgrown CsPbBr 3 single crystals. 17 Figure 1a depicts the typical X-ray diffraction (XRD) pattern of the as-grown CsPbBr 3 single crystal. As shown, the XRD pattern is dominated by the set of (0 0 l)/(h h 0) crystalline plane of orthorhombic CsPbBr 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of perovskite crystals grown by space-confined methods, many ideas were employed to develop large-sized bulk crystals and thin films. For example, Liu et al reported thickness-controllable ultrathin MAPbI 3 SCs by employing a geometry-regulated dynamic flow reaction system. Chen et al employed a facile space-confined solution-processed strategy to grow MPB single-crystalline thin films on substrates in submillimeter dimension.…”
Section: Introductionmentioning
confidence: 99%